Analisis jenjang karir siswa sekolah sepak bola Biting Putra Jaya - Iqbal, Mohammad Iqbal; Rizki Apriliyanto; Ahmad Sulaiman (Physical Education Departement of University PGRI Jombang, 2025)
This study aims to analyze the career development of students at the Biting Putra Jaya (BPJ) Football School (SSB) after participating in the Soeratin U-15 Cup from 2023 to 2025. The research method used was descriptive quantitative with a longitudinal design. The study subjects were 14 students, all of whom were sampled using a total sampling technique. Data were collected through documentation, observation, and interviews with coaches and SSB administrators. Descriptive analysis was conducted by calculating the percentage of student activity each year, the level of competition participated in, and involvement in ongoing coaching activities. The results showed that only 8 students (57.1%) were still actively competing until 2025, while 6 students (42.9%) dropped out or took a break. This decline in participation was influenced by motivational factors, academic priorities, limited facilities, and lack of access to advanced competitions and selection. The study's conclusions confirm that coaching at SSB BPJ has been running quite well at the basic stage, but a long-term athlete development strategy is needed through increased psychological support, academic partnerships, and a sustainable competitive network.